An overlap of angiolymphoid hyperplasia with eosinophilia and Kimura's disease: Successful treatment of skin lesions with cryotherapy - Praveen Kumar S Reddy; Arakali Lakshminarayana Shyam Prasad; Tharayil Kunneth Sumathy; Kanakapura Nanjundaswamy Shivaswamy; Chandrasekaran Ranganathan (Wolters Kluwer Medknow Publications, 2015)
Kimura's disease is characterized by a triad of painless subcutaneous masses, eosinophilia in the peripheral blood and in tissues with marked increase in Serum Ig E. Angiolymphoid hyperplasia with eosinophilia (ALHE) manifests with the presence of dermal papules and nodules. Unique clinical, histopathological, and biochemical findings are noted in these individual entities. A 32-year-female presented with multiple nodules in the axillae for 2 years. Peripheral smear showed eosinophilia with AEC of 6080. Histopathological examination showed features of overlap. Antinuclear antibody immunoflorescence was was negative. CD31, CD34, and FVIII were positive in vascular component. A CT chest revealed left axillary lymphadenopathy. The patient was treated with Cryotherapy and there was complete regression of skin lesions, with no recurrence after 1 year of follow-up. ALHE and KD are common in the head and neck region, but no reports of an overlap, presenting with lesions in the axillae are available to date, to the best of our knowledge. Response of skin lesions to cryotherapy is highlighted.